Investment development of agrarian sector in modern conditions of economic development - Gutkevych, Svitlana; Slobodian, Nataliia (My University, 2021)
The project development of the agrarian sector of the economy is given in the article. Intensification of investment activity in the country is the main goal of economic development. Of great importance for the country's economy are systemic projects aimed at reforming the country's economy. Sectoral projects are aimed at carrying out economic reforms in certain areas. Modeling of the process of investment development of agricultural production is considered.

У статті наведено проект розвитку аграрного сектору економіки. Активізація інвестиційної діяльності в країні є основною метою економічного розвитку. Велике значення для економіки країни мають системні проекти, спрямовані на реформування економіки країни. Галузеві проекти спрямовані на проведення економічних реформ у певних сферах. Розглянуто моделювання процесу інвестиційного розвитку сільськогосподарського виробництва.
Keywords: кафедра міжнародної економіки; investment strategy; economic reforms; economic development; agricultural economy; інвестиційна стратегія; економічні реформи; економічний розвиток; аграрна економіка